Impact of contextual factors on match demands experienced by elite male referees during international basketball tournaments - Iglesias, D. S.; Leicht, A. S.; Pojskic, H.; Vaquera, A. (Journal of Sports Sciences, 2021)
We aimed to assess the cardiovascular responses and locomotory demands of male referees during diverse elite, international, basketball matches, and to investigate the influence of moderating factors (competition sex, level and stage) on these demands. Cardiovascular and locomotory responses were monitored in 123 elite, male referees while officiating 283 basketball sessions (preparation until match end), during group and playoff stages, of women`s and men`s FIBA Continental and World Cups at senior and youth level. The total and average session distance and velocity were ~4740 m, 19.0 m/min and 2 km/h. Referees experienced an average relative HR of 60-65% maximum HR with ~85% of each session spent within the very light to moderate HR categories. The average session relative HR was significantly greater for men compared to women competition, during senior compared to youth sessions, and for the group compared to the playoff stage sessions. Mean distance covered was significantly greater during senior and men compared with youth and women sessions. Elite, international male basketball referees experienced moderate cardiovascular load accompanied with intermittent locomotor activities during international sessions when accounting for all occupational activities. International competitions are more demanding for referees based upon competition sex, level and stage.